Prípad infekce Babesia microti importované do Ceské republiky z USA - Nohýnková, E; Kubek, J; Mĕst'ánková, O; Chalupa, P; Hubálek, Z (Casopis lekaru ceskych, 2003)
Human babesiosis is a zoonotic tick-borne protozoan infection caused by several species of the genus Babesia. It is a rare disease in Europe. Until recently, 31 cases have been described. Most of them were severe infections caused by a cattle parasite Babesia divergens in splenectomized patients. In contrast, a rodent species Babesia microti was responsible for hundreds of cases of human babesiosis in the U.S.A. In this report we describe the first case of human babesiosis in the Czech Republic. To our knowledge, it is also the first case of symptomatic B. microti infection imported to Europe from the United States.
Keywords: Babesia microti; Babesiosis; Travel; Spojené státy americké; Humans; Česká republika; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; cestování; babezióza; United States; Czech Republic